2017
DOI: 10.1371/journal.pgen.1007120
|View full text |Cite
|
Sign up to set email alerts
|

A conserved maternal-specific repressive domain in Zelda revealed by Cas9-mediated mutagenesis in Drosophila melanogaster

Abstract: In nearly all metazoans, the earliest stages of development are controlled by maternally deposited mRNAs and proteins. The zygotic genome becomes transcriptionally active hours after fertilization. Transcriptional activation during this maternal-to-zygotic transition (MZT) is tightly coordinated with the degradation of maternally provided mRNAs. In Drosophila melanogaster, the transcription factor Zelda plays an essential role in widespread activation of the zygotic genome. While Zelda expression is required b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 45 publications
0
51
0
Order By: Relevance
“…The highly anomalous nature of the movement of Zld that differs from that of chromatin associated His2B and Bcd suggests that its motion depends at least in part on interactions off of DNA. Most of the amino acid sequence of Zld consists of intrinsically disordered domains, some of which are required for its function (Hamm et al 2017) . We and others have shown that intrinsically disordered domains mediate weak, multivalent proteinprotein interactions between regulatory factors (Chong et al 2018; Boehning et al 2018; Kovar 2011; Burke et al 2015; Altmeyer et al 2015; Xiang et al 2015; Friedman et al 2007) that lead to the selective enrichment of factors in hubs (Chong et al 2018; Boehning et al 2018 .…”
Section: Our Observation That Zld and Bcd Form Hubs Of Locally High Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly anomalous nature of the movement of Zld that differs from that of chromatin associated His2B and Bcd suggests that its motion depends at least in part on interactions off of DNA. Most of the amino acid sequence of Zld consists of intrinsically disordered domains, some of which are required for its function (Hamm et al 2017) . We and others have shown that intrinsically disordered domains mediate weak, multivalent proteinprotein interactions between regulatory factors (Chong et al 2018; Boehning et al 2018; Kovar 2011; Burke et al 2015; Altmeyer et al 2015; Xiang et al 2015; Friedman et al 2007) that lead to the selective enrichment of factors in hubs (Chong et al 2018; Boehning et al 2018 .…”
Section: Our Observation That Zld and Bcd Form Hubs Of Locally High Cmentioning
confidence: 99%
“…However, how it accomplishes this remains unclear. Zelda has a cluster of four C2H2 Znfingers near the Cterminus that mediate its DNA binding activity and 2 additional ZFs near the Nterminus which have been implicated in controlling its activation potential (Hamm et al 2017) , but most of the rest of the protein consists of varying types of lowcomplexity sequence.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand this surprising result, we examined Zld dynamics in living embryos and particularly during mitosis ( Figure 4). We took advantage of an endogenously tagged fluorescent version of Zld 24 . The GFP-zld flies are homozygous viable, thereby showing that the GFP-tagged version of Zld retains wild-type physiological properties.…”
Section: Quantitative Kinetic Analysis Reveals the Dynamic Propertiesmentioning
confidence: 99%
“…RNAi were expressed following crosses between this recombinant and UASp-shRNA-w (BL35573) or UASp-shRNA-zld 21 , virgin females expressing RNAi, MCP-GFP-His2Av-mRFP were crossed with MS2 containing transgenic constructs. The GFP-zld strain was obtained by CRISPR 24 . GFP-ash1 26 and His2Av-mRFP (BL23651).…”
Section: Drosophila Stocks and Geneticsmentioning
confidence: 99%
“…The functional study of Zelda domains was approached using a Cas9 engineering system to obtain D. melanogaster insects with point mutations in the Zinc finger 1, in the acidic patch, or in the Zinc finger 2 (JAZ) [16]. Mutations in the Zinc finger 1 or in the acidic patch did not affect the viability of the insects, whereas mutations in the Zinc finger 2 (JAZ) led to a maternal-effect lethal phenotype [16]. A transcriptomic analysis of mutated flies showed that the Zinc finger 2 (JAZ) acts as a maternal repressive domain during embryo development, being associated with the transcriptional regulation of the zygotic Zelda targets and with the clearance of maternal transcripts [16].…”
Section: Introductionmentioning
confidence: 99%